"A Miserable Sectarian Spirit": Sectarianism and the Women's Movement in Early Twentieth-Century New South Wales. (1st May 2017) - Rademaker, Laura
Abstract : This article examines the sectarianism that divided feminist organisations in early twentieth-century NSW. In 1903, the Catholic feminist Annie Golding took legal action against the Protestant paper, The Watchman, accusing it of libel. Through an examination of the five leading women embroiled in the Golding affair, this article shows that women activists saw women's political loyalties as potentially divided, not only by questions of labour or free trade but also by religion. Although the feminist organisations the Women's Suffrage League (WSL) and Women's Progressive Association (WPA) each claimed non-sectarian status, in the debates surrounding the Golding case, their leadership proved willing to appeal to sectarian prejudices. When religious presses claimed to find sectarian division among women's organisations, leading feminist women themselves also quickly attributed their differences to religion and exploited what they considered women's natural piety for political gain. These findings contribute to a growing scholarship on the religious dimensions of women's public activism, revealing complex interactions between religion, politics, class and gender.